Urban-dwelling Community Members’ Views on Biomedical Research Engagement - Cortés, Yamnia I. (Qual Health Res, 2016)
In this study, we explore community members’ overall understanding and experience with biomedical research engagement. We conducted a qualitative analysis to explore a concept that emerged, but was not specifically addressed in a pre-existing dataset obtained using four focus group sessions with 30 urban-dwelling community members. Transcripts were read in an iterative process and an emergent content analysis performed. Five main themes were identified: (a) engaging in research to contribute to personal or greater good; (b) hierarchy of trust; (c) the importance of disclosure and transparency; (d) practical barriers to research engagement; and (e) fear of research procedures. Community members view research engagement as a collaborative process whereby community members and researchers are involved in all stages of the investigation. Focusing on research engagement, and not merely participation, may enhance community knowledge of the research process and advance scientific knowledge.